1999
DOI: 10.1099/00221287-145-9-2477
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical characterization of an Ogawa-Inaba common antigenic determinant of Vibrio cholerae O1

Abstract: Cholera remains an important public health problem in many parts of the world and the availability of an effective cholera vaccine is important for the prevention of cholera in the countries affected by this disease. Despite the apearance in 1992 of a new serogroup, O139, of Vibrio cholerae, most of the cholera outbreaks are still caused by V. cholerae O1 biotype El Tor. Vaccine trials in Asia from 1968 to 1971, and studies of the production of serotypespecific antiserum in rabbits and of the protective activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 33 publications
2
36
1
Order By: Relevance
“…1a). As shown by this and previous work (8,37), Abs specific for the terminal perosamine could selectively protect against the Ogawa serotype but would fail to recognize the Inaba serotype. Therefore, protective Abs against both serotypes should bind to the inner part of the O-SP and͞or to sugar residues defining the core of the LPS molecule.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…1a). As shown by this and previous work (8,37), Abs specific for the terminal perosamine could selectively protect against the Ogawa serotype but would fail to recognize the Inaba serotype. Therefore, protective Abs against both serotypes should bind to the inner part of the O-SP and͞or to sugar residues defining the core of the LPS molecule.…”
Section: Resultsmentioning
confidence: 86%
“…The LPS of the Inaba serotype possesses internal structural units common to both Ogawa and Inaba serotypes (35,36), and it has been proposed that both the core and the O-SP (see Fig. 1a) may be involved in this common epitope (37). The crystal structure of the cavity type mAb S-20-4 reported herein confirms the serotype specificity of this and related anti-Ogawa Abs by showing the pivotal contribution by so small a structural fragment in the antigenic determinant as a methyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Serogroup O1 is divided into two major serotypes, Ogawa and Inaba (Stroeher et al 1992). These serotypes differ by their terminal monosaccharides (Villeneuve et al, 1999). V. cholerae O1 Ogawa has been responsible for causing frequent diarrhoeal outbreaks over the last 10 years, although Inaba is becoming increasingly associated with cholera outbreaks (Chhotray et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, the variable heavy chain of mAb I-24-2 differs extensively from those of 72.1 and ZAC-3. Previous studies have suggested that, while mAb ZAC-3 recognizes an epitope at the lipid A or core region, mAb I-24-2 recognizes an epitope at the junction of the core and O-SP region (Lullau et al, 1996;Villeneuve et al, 1999;Wang et al, 1998 In an attempt to determine if the protective epitope that is common to both Ogawa and Inaba serotype LPS can be utilized in a subunit vaccine against cholera, peptide mimics of this epitope were identified by screening phage display libraries with mAb 72.1. Eleven cyclic peptide mimics constrained by two cysteines were identified from three different phage display libraries.…”
Section: Discussionmentioning
confidence: 99%
“…The protective efficacy of ZAC-3 has not been reported. Inhibition studies revealed that the binding of I-24-2 to Ogawa and Inaba LPS may be mediated by a region located at the junction of the O-SP and core region of the LPS (Villeneuve et al, 1999;Wang et al, 1998). The ZAC-3 mAb binds to an epitope in the lipid A or core region but not to the O-SP (Lullau et al, 1996).…”
Section: Introductionmentioning
confidence: 99%